Efeito do corante Vermelho de sudan B na marcaçao e no desenvolvimento de Diatraea saccharalis ( Fabricius, 1794) (Lepidoptera: Crambidae) e de Cotesia flavipes (Cameron, 1891) ( Hymenoptera: Braconidae) - Volpe, H.X.L.; Vacari, A.M.; Veiga, A.C.P.; Viel, S.R.; De Bortoli, S.A. (My University, 2009)
The objective of this work was to evaluate biological aspects of Diatraea saccharalis fed on artificial diet containing different concentrations of the Sudan B Red dye and the possibility to mark the parasitoid Cotesia flavipes, when submitted to the parasitism of dyed caterpillars. For that, were added to the artificial diet four concentrations of Sudan Red B dye (100, 200, 300 and 400 ppm) and control (no dye addition). It was evaluated larval and pupal period, larval and pupal viability, longevity, sex rate, pupal weigh, eggs per female, eggs per day, number of eggs per egg mass, egg viability and embrionary period; besides same were accomplished measurements in the caterpillars (bioassay I). Caterpillars of 17 days old (30) of each treatment were removed from the tubes and exposed to the parasitism of C. flavipes (bioassay 2). The egg-pupae period, sex rate, pupal period and viability, number of females, males, total of emerged adults and longevity were evaluated. The data were submitted to the multivariate analisys methods: cluster analysis, two-way and principal component analysis. Based on analysis, it was observed that the treatment of 100 ppm was the least harmful to the biology of the sugar cane borer larvae by groping to the control and did not influence negatively its biological aspects. The concentration of 400 ppm affected negatively the biology of C. flavipes. The Sudan Red B it is ended doses marked the caterpillars and the adults, however the concentration of 100 ppm is the most suitable to dye D. saccharalis. None of the tested concentration marked adults of C. flavipes, despite to affect negatively its biology. It is unviable to increase the concentration seeking futures tests, for that dye to be harmful to the biological aspects of D. saccharalis and C. flavipes.
Effect of Sudan Red B dye in the mark and development of Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) and Cotesia flavipes (Cameron, 1891) (Hymenoptera: Braconidae).